2018
DOI: 10.18805/lr-400
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mixture ratio and cutting time on forage yield and silage quality of intercropped berseem clover and italian ryegrass

Abstract: The research was carried out to determine the effects of different mixture ratios and cutting times on dry-matter yield and silage quality of mixtures of bersem clover (Trifolium alexandrinum L.) with Italian ryegrass (Lolium multiflorum Lam.) in Adana province, Turkey. The experiment was laid out in split plot design with four replications during the years of 2011-2013. The mixture-ratios ( 80% BC + 20% IR, 60% BC + % 40 IR, 40% BC+ % 60 IR, 20% BC + 80 % IR, pure berseem clover (BC) and Italian ryegrass (IR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 13 publications
5
13
1
Order By: Relevance
“…Many investigators also reported an increase in CP as a result of the increase in legume ratio in mixtures. Parallel to our findings, increasing amount of legumes in the mixture of silage resulted with increases in CP content in studies like that of Yücel et al, (2018a) and Seydosoglu and Gelir, (2019).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Many investigators also reported an increase in CP as a result of the increase in legume ratio in mixtures. Parallel to our findings, increasing amount of legumes in the mixture of silage resulted with increases in CP content in studies like that of Yücel et al, (2018a) and Seydosoglu and Gelir, (2019).…”
Section: Resultssupporting
confidence: 88%
“…Aykan and Saruhan (2018) mixed different ratios of forage pea and barley and reported that the highest score was obtained from sole barley silage where ADF and NDF of sole forage pea silage was lower than sole barley silage. Yücel et al (2018a) mixed Italian grass and berseem clover and informed that they observed the most appropriate silage quality values were obtained with 60% Italian grass + 40% berseem clover mixture. Seydosoglu and Gelir (2019) informed that, in the silage of barley-grass pea mixture, silage pH value increased with the higher inclusion of grass pea in the mixture.…”
Section: Introductionmentioning
confidence: 89%
“…They also found that the 50:50 maize-soybean ratio was the optimum giving highest forage yield, proteincontent and protein yield. Yucel et al, (2018) conducted a research with mixtures of bersem clover (Trifolium alexandrinum L.) with Italian ryegrass (Lolium multiflorum Lam.) and concluded that the mixture of 60 % bersem clover + 40 % Italian ryegrass, harvested at full flowering of bersem clover was superior in terms of dry matter yield and silage quality.…”
Section: Introductionmentioning
confidence: 99%
“…In studies related to berseem clover, results of Hakyemez and Sancak (2005) shown similar in terms of forage yield and quality. But results of Yucel et al (2018) shown some differences.…”
Section: Resultsmentioning
confidence: 85%
“…Derya was evaluated as material and 0,02 t ha -1 seed was used (Acıkgoz, 2001). The mowing process was carried out from a height of 5 cm with the mower (Bcs 615 L Max Honda Gx200) when the plants reached 50-100% flowering time according to Yucel et al (2018). Ten different plants were taken from the parcels for the measure of plant height (cm), stem diameter (mm) and leaf/stem ratio (%).…”
Section: Methodsmentioning
confidence: 99%